Strategi Unit Pelaksana Teknis Daerah (UPTD) Kampung Anak Negeri dalam Membangun Karakter Mandiri pada Anak Tunagrahita di Kalijudan Surabaya - Yunita Abdilah; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2025)
Independent character is an important aspect that must be instilled in every child. Children with intellectual disabilities tend to be less independent and still rely on others due to developmental delays. This research aims to describe the strategies used by UPTD Kampung Anak Negeri Kalijudan in developing independent character in children with intellectual disabilities, as well as to describe the supporting and inhibiting factors in building independence among these children. This study uses Edward L. Thorndike’s theory of connectionism. A qualitative research approach with a descriptive method was employed. The research subjects were determined using purposive sampling, and the subjects included the head of the institution, caregivers, and children with intellectual disabilities. Data collection techniques included observation, interviews, and documentation. Data analysis involved data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the strategies implemented by UPTD Kampung Anak Negeri Kalijudan to foster independence in children with intellectual disabilities include: 1) Establishing a close approach to the children, 2) Encouraging non-dependence on others, 3) Instilling a sense of responsibility, 4) Habituation, 5) rewards and punishments, and (6) Facilitating and developing the potential of children with intellectual disabilities. The supporting factors in developing independence are: (1) Supportive policies from UPTD Kampung Anak Negeri Kalijudan, 2) Adequate facilities, 3) The children with intellectual disabilities, and 4) Cooperation among caregivers. The inhibiting factor is that some children are unwilling to follow existing rules .